2016
DOI: 10.18632/oncotarget.11854
|View full text |Cite
|
Sign up to set email alerts
|

NTS/NTR1 co-expression enhances epithelial-to-mesenchymal transition and promotes tumor metastasis by activating the Wnt/β-catenin signaling pathway in hepatocellular carcinoma

Abstract: Neurotensin (NTS) is a neuropeptide distributed in central nervous and digestive systems. In this study, the significant association between ectopic NTS expression and tumor invasion was confirmed in hepatocellular carcinoma (HCC). In primary HCC tissues, the NTS and neurotensin receptor 1 (NTR1) co-expression (NTS+NTR1+) is a poor prognostic factor correlated with aggressive biological behaviors and poor clinical prognosis. Enhanced epithelial-to-mesenchymal transition (EMT) features, including decreased E-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 43 publications
(42 reference statements)
5
33
0
Order By: Relevance
“…Blocking the NTSR1 signaling by the specific antagonist SR48692 inhibited the activity of Wnt/β-catenin signaling. Consistent with our observation, Ye et al found that NTS-induced epithelial-to-mesenchymal transition (EMT) was correlated with the remarkable increase in Wnt1, Wnt3, Wnt5 expression and p-GSK3β level [9]. Furthermore, NTSR1 expression in hepatocellular carcinoma (HCC) was also positively correlated with the alteration of the Wnt/β-catenin pathway [17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Blocking the NTSR1 signaling by the specific antagonist SR48692 inhibited the activity of Wnt/β-catenin signaling. Consistent with our observation, Ye et al found that NTS-induced epithelial-to-mesenchymal transition (EMT) was correlated with the remarkable increase in Wnt1, Wnt3, Wnt5 expression and p-GSK3β level [9]. Furthermore, NTSR1 expression in hepatocellular carcinoma (HCC) was also positively correlated with the alteration of the Wnt/β-catenin pathway [17].…”
Section: Discussionsupporting
confidence: 87%
“…2A, inhibition of NTSR1 with SR48692 or NTSR1 knockdown resulted in a significant decrease in the phosphorylation level of NF-κB and MAPK, suggesting the downstream cascades of NTS/NTSR1 signaling. Previously, it has been reported that exogenous NTS stimulation can upregulate the expression of Wnt proteins in liver cancer [9]. To test this hypothesis in glioblastoma, we detected the effects of NTS on the expression of Wnt1, Wnt3a and Wnt5a upon NF-κB and MAPK inhibition.…”
Section: Resultsmentioning
confidence: 98%
“…In our hands, the PLC/PRF5 cells were highly invasive, overexpression of NTSR1 did not markedly change these characteristics. Collectively, these data suggest that the NTS and NTSR1 promote the invasiveness and migration of HCC cells, and corroborate the data previously published for HCC [32] and breast cancer [6].…”
Section: Nts/ntsr1 Complex Enhances Migration and Invasion Of Hcc Cellssupporting
confidence: 91%
“…This pathway alters many different liver functions, and contributes to hepatocyte transformation by directly or indirectly regulating many genes at the transcription level including NTSR1. Interestingly, a recent study proposed that NTS/NTSR1 signaling enhanced epithelial/mesenchymal transition by activating Wnt/b-catenin signaling [32]. Together the data from these two papers suggest a feed forward regulation of the NTSR1 signaling on abnormal b-catenin signaling.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation